Increasing work engagement through the roles of transformational leadership, perceived organizational supports, and work motivation (study at SMA Negeri 2 Mranggen, Demak, Indonesia) - Pravira Noer Fadlila; Rohmini Indah Lestari; Albert (Pusat Riset dan Inovasi Nasional, 2025)
This analysis is intended to evaluate the impact of transformational leadership and perceived organizational support on educators' work attachment at SMA Negeri 2 Mranggen, Demak Regency, with work motivation placed as an intermediate variable. This study seeks to close the gap from previous research that showed mixed results related to the relationship between these variables. The approach used in this analysis is in the form of a survey with an explanatory research design. The subjects of the analysis included all teaching staff at SMA Negeri 2 Mranggen, Demak Regency, which amounted to 67 people, as well as being used as a sample through the total sampling technique. The main data sources were obtained using questionnaires and interviews, then processed using the Partial Least Square (PLS) method using the SmartPLS application version 4.0. The findings of the analysis confirm that transformational leadership and work motivation have a positive and significant influence on work attachment. However, the perceived organizational support does not have a significant influence on work attachment, either directly or through work motivation as a mediating variable. This indicates that work motivation is not able to bridge the influence of transformational leadership and perceived organizational support on work attachment.